The effect of the early "skin-to-skin contact" method on breastfeeding - Miolski, Jelena; Raus, Mišela; Radusinović, Milica; Zdravković, Vera (Medicinski časopis, 2023)
Introduction: The task of public health is to encourage the mother to initiate and maintain breastfeeding of her child. The main proponents of early breastfeeding should be pediatricians and gynecologists in maternity hospitals. Early "skin-to-skin" contact means that after birth, in the first ten minutes, the newborn is placed in close contact with the mother. After it is born and cries, it is carried and placed on the bare chest of the mother, who is comfortably placed with her head elevated. The child is placed in a longitudinal position in relation to her, between and above her breasts. The child’s head is turned to the side with mandatory monitoring of breathing, and both are covered with a clean, dry sheet. The basis of the mechanism is hormonal. With this kind of mutual contact, oxytocin is released in the mother, and catecholamine concentrations increase in the newborn. The first two hours after birth, the newborn is awake, active, sensitive to touch, smell and temperature simulations that he receives from the mother, which is why this period is the best for starting breastfeeding. The advantages of this method for the mother are: easier and faster stopping of bleeding after childbirth, earlier expulsion of the placenta, greater calmness and relaxation, as well as greater self-efficacy in breastfeeding. The advantages for the newborn are: reduction of postpartum stress and anxiety, less crying, better control of reaching optimal body temperature, importance in establishing microcolonization of the intestinal flora and more effective breastfeeding with earlier discharge from the hospital to home. Conclusion: The application of this method is simple and economically profitable, and short-term and long-term effects are achieved for both the mother and the child.